Study of Psychological Distresses in Married Children Caring for Their Aging Parents: A Qualitative Study - Ahmad Aghajani (Sālmand, 2018)
Objectives Considering the phenomenon of aging population in societies like Iran, and increasing pressure of caring for elderly people on middle-aged generations, as well as the need to have a regional view to the subject, this study aims to identify psychological distresses in married children who should take care of their elderly parent(s). Methods & Materials This research was carried out qualitatively by means of phenomenological approach. The study field was the married caregivers of their parent(s) who lived in Qom City, Iran, in 2016. The participants (13 males and females) were selected with purposeful sampling method through referring to the related institutions. Sample size was determined through theoretical saturation. The relevant data were collected using deep interview with the participants, and data analysis was carried out using 7-step method of Colaizzi. Results The psychological distresses experienced by the participants were categorized into 3 main categories, 7 subcategories, and 39 concepts. The first category contains unpleasant excitements that includes two subcategories of emotions and concerns. The second category embraces the neurotic states, which includes three subcategories: depression, anxiety, and obsession. And the third category embodies conflicts, which covers the two subcategories of role conflict and doubts. Conclusion The care of the elderly parent(s) for married children who are already involved in several tasks have undesirable psychological outcomes which were identified in this study. The results of this research can be considered as the basis for providing psychological services and counseling to the target population. They can also motivate quantitative and statistical research based on existing findings.